Implementation of Learning Mockup of the Great Mosque Demak History of Islamic Acculturation - Anggraini, Dila Putri; Ayundasari, Lutfiah (Program Magister Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
This research contains a study on the application of mock-up media in history learning in Islamic acculturation materials. The main purpose of this study is to examine the application of mock-up media of the Great Mosque of Demak in learning the history of acculturation materials of the Islamic Kingdom. In addition to being a learning medium for the history of the Demak Grand Mosque mockup, it also has the potential to be used as an enrichment in learning Islamic History and Islamic Religious Education. The method used in this study is qualitative descriptive, which focuses on depicting phenomena in depth. The stages in this study consist of data collection, data filtering, presentation of results, and drawing conclusions or validating data. Information was collected from observations, documentation, interviews with history subject teachers, deputy heads of curriculum and X DKV students participating as research subjects. The results of the study show that the implementation of learning media using mockups can give a real impression of the object of the Great Mosque of Demak. History learning using a mock-up of the Great Mosque of Demak provides a better understanding for students regarding the form of acculturation of Islamic culture with the archipelago. The results of the evaluation show that the implementation of learning using a mock-up of the Great Mosque of Demak can illustrate the ability of students to develop. The use of mock-up media of the Great Mosque of Demak can make it easier for teachers to explain learning materials and create contextual learning so that learning goals are achieved.